Outcome after polyaxial locking plate osteosynthesis in proximal tibia fractures (VALCP ® vs. NCB-PT®): a prospective randomized clinical trial. Issue 5 (28th May 2020) - Völk, Dominik; Neumaier, Markus; Einhellig, Heike; Biberthaler, Peter; Hanschen, Marc
Aims and Objectives: The use of polyaxial locking plates is an established technique for the treatment of proximal tibia fractures. At the moment different polyaxial locking implants from numerous manufactures are available, though at the moment there are no clinical trials regarding their differences. In this prospective clinical trail we compared the NCB-PT® (Zimmer) and the VA-LCP® (Synthes) by analysing primary and secondary quality criteria of the osteosynthesis (clinical and radiological). Materials and Methods: This study enrolled 28 patients suffering from a proximal tibia fracture (AO/ASIF 41 B-C). The follow-up examinations were conducted over 12 months after the surgery. Clinical (e.g. range of motion, Rasmussen score, Tegner score) as well as radiological parameters (e.g. primary and secondary loss of reduction, fracture healing) were collected. For the analysis of continuous parametric variables the Student's t-test was used and for non-parametric variables the Mann-Whitney U test. For binominal variables the Fisher's exact test was preformed. In all analysis the significance level was set at a p-value <0, 05. Results: Comparing the epidemiologic data of both groups only very small or no differences with no statistical significance could be found. The intraoperative data showed a significant longer surgery duration for the NCB-group (NCB-PT® 196, 3 min vs. VA-LCP® 121, 7 min, p-value 0, 0335). Furthermore the median length of implants used in each group proved to be significant longer in the NCB-group (NCB-PT® 8, 1 holes vs. VA-LCP® 5, 1 holes, p-value 0, 0007), most likely because of the imbalance of severe fractures in between the groups (type C fractures: NCB-PT® 78% vs. VA-LCP® 26%). The analysis of the clinical data as well as the clinical scores showed reduced scoring values of the NCB-group. Only the results of the Lysholm score (p-value: 0, 03) and MKQ (Munich Knee Questionnaire) (p-value: < 0, 0001) proved to be statistically significant. Regarding the radiological data only the radiologic Rasmussen score had a significant difference in favour of the VA-LCP®-group (p-value 0, 0153). Conclusion: This study constitutes the first prospective clinical trial to compare the outcome of the VALCP® an NCB-PT® for the treatment of proximal tibia fractures. Despite the limitation of this study, low case numbers and heterogeneity of fracture types, differences regarding the clinical and radiological outcome could be found. The treatment with the VA-LCP® had a significantsuperior outcome in separate clinical scores (Lyshom score/ Munich Knee Questionnaire) as well as in a single radiologic score (radiologic Rasmussen score) in comparison to the treatment with the NCB-PT®. Our data underlines the necessity for an extended study with a higher case number.